Contribuições do Programa Institucional de Bolsas de Iniciação Científica (PIBIC) para a formação do aluno de psicologia - Oliveira, Andressa Maia de (2013)
The undergraduate courses in Psychology have been historically pointed as defective in aspects related to the critical education and the integration between theory and practice. Hence, the scientific education has been considered a possibility to overcome those lacks. Therefore, this study has investigated the undergraduate education process of Psychology students with PIBIC (Portuguese acronym for Undergraduate Scientific Research Scholarships Institutional Program) scholarships from CNPq (Portuguese acronym Brazilian National Council of Scientific and Technological Development). The scholarship program has been a strategic tool for the undergraduate scientific research. Electronic questionnaires have been sent to all the PIBIC scholarship students of Psychology in Brazil (622; 104 have answered), containing questions about the program developed activities, tutoring and advising, PIBIC evaluation and other ones. The students scientific and academic production has also been investigated through their Lattes (CNPq s Platform in which researchers have their academic résumés). The major part of the participants (70%) has stated that the first motivation to be in the program had been their interest in the research or in the academic career. Furthermore, 60% of the scholarship students has worked as volunteers before receiving PIBIC scholarship. Among the students who have answered the research, 65,4% has reported they are tutored directly by their advisors, and 80% of them attends one or more than one advising meeting every fifteen days. It has been identified that the Psychology scholarship students do not participate in all the research activities and that the proximity with the advisor is related to the accomplishment of tasks which contributes with the student critical and reflexive education. Finally, less than 25% of the students has published scientific articles or book chapters during the scholarship, what XI demonstrates a possible exclusion of them in that phase of the process. In general, the scholarship students evaluate the program positively by revealing that it contributes with their professional and academic education. For those reasons, it is observed PIBIC s potential role for the undergraduate education in order to develop more critical psychologists able to propose innovations and contextualized practices. However, the results obtained in programs like the studied one denounce the disqualification of the provided undergraduate education for the major part of the university students, who do not have a PIBIC scholarship. As a result, it is emphasized that it there should be more investment for improving the quality of the undergraduate education itself and not only for programs which are available for few students